Estudio de prefactibilidad para la instalación de una planta productora de calzado de biocuero para dama con plantilla a base de canela - Amoros Lara, Alejandra Lucia (2020)
This document responds to the need to make a positive change in the environment, thus helping sustainable development. The purpose preliminary study for the implementation of an ecological footwear plant based on vegetable leather for women is to present the technical, economic, social and environmental viability of the plant, through quantitative and qualitative methods. When carrying out the pertinent studies, he tells us that the footwear world has a positive tendency to take care of the environment, since companies already use it in the manufacture of recyclable material footwear. At chapters I, II and III we detail the general aspects of the research, the market study is carried out, which aims to calculate and identify the target market of the project through a survey to determine different indicators. In addition, we determine the most appropriate location for the plant considering different factors, the result of this evaluation was Lurin district.At chapters IV and V the plant capacity was established, which in our case was determinated by the pressing machine. The characteristics of the product and the requirements necessary for production were also delimited. Finally, at chapters VI, VII and VIII, the administrative and productive organization of the company was defined and the economic, financial and social evaluations made to the project are shown. As a result, we obtain a VANE and VANF of S / 1.1 MM and S / 4.3 MM, respectively, while the TIRE is 34.4% and the TIRF is 150%.